MANAGEMENT OF ECTOPIC VARIX WITH HISTOACRYL - Khan, Adil Naseer; Kiani, Ismaa Ghazanfar; Arshad, Muhammad; Hidayat, Rania; Said, Khalid; Shehzad, Aamir (Journal of Ayub Medical College Abbottabad, 2014)
Upper gastro-intestinal (GI) bleed is one of the most serious situations encountered in the emergency department. There is consensus regarding management of common causes of upper GI bleed but for rare causes no such consensus exists. We present a case of a 35 year old male who presented with 5-6 episodes of hematemesis associated with melena in 24 hours. On examination he was in hypotensive shock with no stigmata of chronic liver disease. Doppler studies showed portal vein thrombosis with cavernous transformation and varices in peripancreatic region and around duodenum. His upper GI endoscopy showed a large varix with ulceration in the duodenal bulb, indicating it as the source of bleeding. The varix was injected with 1cc of cyanoacrylate. The patient’s final diagnosis was non-cirrhotic portal hypertension secondary to portal vein thrombosis. At immediate and long term follow-up the patient had no complications. We conclude that cyanoacrylate injection effectively manages ectopic duodenal varices and can be used with a simple application technique. Keywords: Ectopic varices, hematemesis, upper gastro-intestinal endoscopy